2015
DOI: 10.1158/1078-0432.ccr-15-0242
|View full text |Cite
|
Sign up to set email alerts
|

Notch Pathway Inhibition Using PF-03084014, a γ-Secretase Inhibitor (GSI), Enhances the Antitumor Effect of Docetaxel in Prostate Cancer

Abstract: Purpose To investigate the efficacy and mechanisms of Notch signaling inhibition as an adjuvant to docetaxel in castration-resistant prostate cancer (CRPC) using a γ-secretase inhibitor (GSI), PF-03084014. Experimental Design The effect of PF-03084014 on response to docetaxel was evaluated in docetaxel-sensitive and -resistant CRPC cell lines in vitro and in murine models. Both soft tissue and bone sites were evaluated in vivo. Impacts on cell proliferation, apoptosis, cancer stem cells and angiogenesis were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 48 publications
3
83
1
Order By: Relevance
“…Additionally, GSI treatment delays the tumor growth of prostate cancer xenografts. Consistent with our findings, previous study has shown that the GSI PF-03084014 results in a significant decrease in tumor growth in two xenograft models of prostate cancer (PC3 and DU145) (12). PF-03084014 demonstrated an even greater antitumor effect in prostate cancer growth when combined with the chemotherapeutic agent docetaxel, which is currently in clinical use (12).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, GSI treatment delays the tumor growth of prostate cancer xenografts. Consistent with our findings, previous study has shown that the GSI PF-03084014 results in a significant decrease in tumor growth in two xenograft models of prostate cancer (PC3 and DU145) (12). PF-03084014 demonstrated an even greater antitumor effect in prostate cancer growth when combined with the chemotherapeutic agent docetaxel, which is currently in clinical use (12).…”
Section: Discussionsupporting
confidence: 91%
“…Elevated expression of the Notch ligand Jagged1 has been associated with metastatic prostate cancer (8,9), and downregulation of Notch1 and Jagged1 in human prostate cancer cell lines decreases in vitro invasion and cell growth (10). In addition, chemoresistance in human prostate cancer cells has been linked to the activation of Notch2 receptors (11,12). Despite these studies, direct evaluation of Notch receptors as drivers of aggressive prostate cancer and the relationship of Notch receptors with other commonly altered pathways in prostate tumorigenesis remain unclear.…”
mentioning
confidence: 99%
“…49 GSI inhibitor suppressed Notch pathway and enhanced the antitumor effect of docetaxel in prostate cancer. 50 Recently, one study validated that activation of Notch-1 synergized with multiple pathways in promoting castration resistant prostate cancer. 51 Therefore, identification of precise mechanisms that regulate EMT process would likely be useful for exploring novel therapeutic approaches for the treatment of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…PF-03084014 (PF-4014) is a GSI developed by Pfizer, which shows antitumor efficacy in hematologic, breast, colorectal, and pancreatic cancer models (13)(14)(15)(16)(17)(18), and suppresses hepatic metastases of neuroblastoma and breast cancer cells (19). Currently PF-03084014 is in phase I or phase II trials for the treatment of T-ALL, lymphoma, desmoid tumors, and fibromatosis (4,20,21).…”
Section: Introductionmentioning
confidence: 99%